Role of citicoline and choline in the treatment of post-stroke depression: an exploratory study - Francesca Antonia Arcadi (SAGE Publishing, 2021)
Objective To compare selective serotonin reuptake inhibitors (SSRIs) and nootropic drugs in the reduction of anxiety and depressive symptoms in post-stroke patients. Methods This retrospective cohort study included patients diagnosed with post-stroke depression that were treated with either SSRIs or nootropic drugs (i.e. citicoline or choline alphoscerate). Depression and anxiety were assessed using the Hamilton Rating Scales. Statistical associations between the use of nootropic drugs and mood disorder improvements were determined by measuring assessment scores at 6-months. Results A total of 44 post-stroke patients with depression (aged 45–75 years) were enrolled in the study: 20 were treated with SSRIs and 24 received nootropic drugs. From baseline to follow-up, the SSRI group showed a large effect size with regard depression (success rate difference [SRD] 0.57; 95% confidence interval [CI] 0.21, 0.79) and anxiety (SRD 0.49; 95% CI 0.14, 0.74), whereas the nootropic group showed a small effect size for depression (SRD 0.16; 95% CI –0.17, 0.46) and a small effect size for anxiety (SRD 0.36; 95% CI –0.03, 0.62). Conclusion The administration of nootropic drugs could be a valid therapeutic strategy to manage post-stroke patients suffering from mild–moderate anxiety or anxious-depressive syndrome, but this requires further research.